Methylation of Elongation Factor 1A: Where, Who, and Why?. Issue 3 (March 2018) - Hamey, Joshua J.; Wilkins, Marc R.
Abstract : Eukaryotic elongation factor 1A (eEF1A) is an essential and highly conserved protein involved in diverse cellular processes, including translation, cytoskeleton organisation, nuclear export, and proteasomal degradation. Recently, nine novel and site-specific methyltransferases were discovered that target eEF1A, five in yeast and four in human, making it the eukaryotic protein with the highest number of independent methyltransferases. Some of these methyltransferases show striking evolutionary conservation. Yet, they come from diverse methyltransferase families, indicating they confer competitive advantage through independent origins. As might be expected, the first functional studies of specific methylation sites found them to have distinct effects, notably on eEF1A-related processes of translation and tRNA aminoacylation. Further functional studies of sites will likely reveal other unique roles for this interesting modification. Highlights: eEF1A is a highly modified protein involved in many different cellular processes, including translation, actin cytoskeleton organisation, proteasomal degradation, and nuclear export. It has been known for decades that eEF1A contains many methylated residues; despite this, the responsible methyltransferases were not known. Recent studies have uncovered nine novel methyltransferases, four in human and five in yeast, that target specific eEF1A residues. Some of these enzymes are conserved from yeast to human. eEF1A methyltransferases come from diverse methyltransferase families, including two families that were only discovered recently. Knockout studies of three human eEF1A methyltransferases suggest a role for methylation in eEF1A-related processes, such as translation and tRNA aminoacylation.